Método digital para la detección de la dirección del flujo sanguíneo en sistemas Doppler ultrasónicos - Sotomayor, A.; Fuentes, M.; García Nocetti, F.; Moreno, E.; Barragán, M. (Revista Mexicana de Ingenieria Biomedica, 2002)
Doppler ultrasound systems are widely used for studying blood flow and diagnosis of vascular diseases. An important characteristic of these systems is the ability to detect the direction of the flow of blood accurately. Most Doppler ultrasound systems apply a quadrature demodulation technique on the ultrasonic transducer output signal. Therefore additional treatment is necessary to separate forward and reverse flow signals. This work presents a digital method to convert signals in quadrature into directional signals using an FFT approach. Validating of the method has been achieved using simulated Doppler ultrasound signals.